Increase of suicide and accidental death after hematopoietic stem cell transplantation. Issue 11 (19th March 2013) - Tichelli, André; Labopin, Myriam; Rovó, Alicia; Badoglio, Manuela; Arat, Mutlu; van Lint, Maria Teresa; Lawitschka, Anita; Schwarze, Carl Philipp; Passweg, Jakob; Socié, Gérard
<x xml:space="preserve">Abstract</x> BACKGROUND Relapse and transplant‐related complications are leading causes of mortality after hematopoietic stem cell transplantation (HSCT). Suicides and accidents have not been studied in these patients. This study sought to determine whether there is an excess of suicide and accidental deaths after HSCT, and to determine risk factors. METHODS The incidence of suicidal and accidental death in patients after undergoing HSCT, standardized mortality ratio (SMR), and absolute excess risk (AER) of suicide and accidental deaths was determined, compared with the general European population. A case‐control analysis was done to define factors associated with suicide and accidental deaths. Data were derived from the European Group for Blood and Marrow Transplantation Registry, including 294, 922 patients who underwent autologous or allogeneic HSCT from 1980 to 2009. RESULTS The 10‐year cumulative incidence of suicide and accidental deaths was 101.8 and 55.6 per 100, 000 patients, respectively. SMR and AER of suicide after HSCT were 2.12 (P < .001) and 10.91, higher than in the European general population for 100, 000 deaths, respectively. SMR and AER of accidental death were 1.23 (P < .05) and 2.54, respectively. In the case‐control study, relapses were more frequent among patients who committed suicide after autologous HSCT (37% versus 18%; P < .0001). Chronic graft‐versus‐host disease was higher among patients who committed suicide after allogeneic HSCT (64% versus 37%; P = .001). CONCLUSIONS There is an excess of deaths due to suicide and accidents in patients after undergoing HSCT as compared with the European general population. Relapse was associated with more suicide and accidental deaths after autologous HSCT, and chronic graft‐versus‐host disease was associated with more deaths by suicide after allogeneic HSCT. Cancer 2013;119:2012–2021. © 2013 American Cancer Society.